2023
DOI: 10.1021/acscatal.2c05898
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Speciation and Propane Dehydrogenation in Zn/H-ZSM-5 Catalysts

Abstract: Zn/H-ZSM-5 catalysts have been frequently investigated for propane dehydrogenation (PDH); however, the active site remains unresolved due to the complexity of the system. We employed in situ FTIR spectroscopy and a kinetics method to correlate the Zn speciation and PDH activity in Zn/H-ZSM-5 with two Si/Al ratios (15 and 39) and a range of Zn/Al ratios (0–1.7). Incremental additions of zinc show that Zn2+ sites are preferentially formed on H-ZSM-5 over a fraction of paired Al sites followed by [Zn-O-Zn]2+ and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…The propylene selectivity remained above 95% throughout the test. Compared to the state-of-the-art Zn-based PDH systems, , ,, ZnO@MFI-P exhibits a higher propylene formation rate and relatively lower deactivation rate, as summarized in Table S1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The propylene selectivity remained above 95% throughout the test. Compared to the state-of-the-art Zn-based PDH systems, , ,, ZnO@MFI-P exhibits a higher propylene formation rate and relatively lower deactivation rate, as summarized in Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…The higher amounts of hydroxyl nests contribute to Zn oxo formation and achieve exceptional PDH performance. Based on the above studies, it can be found that various synthetic methods lead to the formation of multiple Zn species including isolated Zn 2+ , [ZnOH] + , Zn oxo , ZnO x clusters, and bulk ZnO aggregates . Moreover, several studies have observed the in situ Zn site evolution during the PDH reaction or H 2 pretreatment. , The multiple Zn species and dynamic evolution make it challenging to identify the structure of the real active Zn sites under working conditions, which restrains further catalyst optimization.…”
Section: Introductionmentioning
confidence: 99%
“…ZnO-supported zeolites are potential high-temperature dehydrogenation catalysts. , Zhao et al utilized the physical mixing method of ZnO and silicalite-1 zeolite to synthesize supported ZnO x species by the reduction treatment above 550 °C (Figure m) Figure n).…”
Section: Non-noble Metal Oxide Catalystsmentioning
confidence: 99%
“…[8] Recently, Yuan et al proposed insights on the formation of ZnO species (single Zn 2 + site, [ZnÀ OH] + site, [ZnÀ OÀ Zn] 2 + site, and ZnO x clusters) on H-ZSM-5 catalysts with different Si/Al and Zn/Al ratios. [9] The results showed that the [ZnÀ OH] + and [ZnÀ OÀ Zn] 2 + sites were more superior than the single Zn 2 + site in PDH reaction, especially for the stability of ZnÀ OÀ Zn. In addition, amorphous SiO 2 supported with Zn single sites (tetrahedrally coordinated single Zn (II) sites) were also developed as efficient PDH catalyst, in which the heterolytic cleavage mechanism was favorable for increasing the selectivity for alkane dehydrogenation.…”
Section: Introductionmentioning
confidence: 96%